Comparison of cutout resistance of dynamic condylar screw and proximal femoral nail in reverse oblique trochanteric fractures: A biomechanical study - Cheema G.S.; Rastogi A.; Singh V.; Goel S.C.; Mishra D.; Arora S. (My University, 2025)
Background: Reverse oblique trochanteric fracture of femur is a distinct fracture pattern. 95° Dynamic condylar screw (DCS) and proximal femoral nail (PFN) are currently the most commonly used implants for its fixation. This study aims to biomechanically compare the cutout resistance as well as modes of failure of DCS and PFN in reverse oblique trochanteric fractures. Materials and Methods: Sixteen freshly harvested cadaveric proximal femoral specimens were randomly assigned to three mean bone mineral density matched groups, eight of which were implanted with 95 DCS and the other eight with PFN. The constructs were made unstable to resemble a reverse oblique trochanteric fracture by removing a standard size posteromedial wedge. These constructs were subjected to computer controlled cyclic compressive loading with 200 kg at a frequency of 1 cycle/second (1 Hz) and end points of both the groups were analyzed. Results: The bending moment of the PFN group was approximately 50% less than that of the DCS group (P<0.0001). The PFN group resisted more number of cycles than the DCS group (P=0.03) and showed lesser number of component failures as compared with the DCS group (P=0.003). Conclusions: The PFN is biomechanically superior to DCS for the fixation of reverse oblique trochanteric fractures of femur.